Anthropomorphic Blast Test Device for Primary Blast Injury Risk Assessment. (19th February 2020) - Hsu, Yun; Ho, Kevin; Chan, Philemon
Abstract: Introduction: Blast overpressure health hazard assessment is required prior to fielding of weapon systems that produce blast overpressures that pose risk of auditory and nonauditory blast lung injuries. The anthropomorphic blast test device (ABTD) offers a single device solution for collection of both auditory and nonauditory data from a single blast at anthropometrically correct locations for injury risk assessment. It also allows for better replication of personnel positioning during weapons firings. The ABTD is an update of the blast test device (BTD), the current Army standard for collection of thoracic blast loading data. Validation testing of the ABTD is required to ensure that lung injury model validated using BTD collected test data and sheep subjects is still applicable when the ABTD is used. Methods: Open field validation blast tests were conducted with BTD and ABTD placed at matching locations. Tests at seven blast strength levels were completed spanning the range of overpressures for occupational testing. Results: The two devices produced very similar values for lung injury dose over all blast levels and orientations. Conclusion: The ABTD was validated successfully for open field tests. For occupational blast injury assessments, ABTD can be used in place of the BTD and provide enhanced capabilities.